2021
DOI: 10.1088/1755-1315/845/1/012123
|View full text |Cite
|
Sign up to set email alerts
|

Functional meat and vegetable pate with spirulina

Abstract: Fundamental research has extensively described the various biological and medical effects of consuming the microalgae spirulina or its constituents. A number of studies indicate an increase in the immune response when they are used for the manifestation of anti-inflammatory, antidiabetic and other important properties. The composition of spirulina and its biological effects make it a unique dietary supplement, the inclusion of which in food products will provide them with functional properties. It has been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…When Laminaria japonica (Sea tangle) powder was added to patties [ 22 ] and breakfast sausages [ 23 ] in a concentration of 5% and 4%, respectively, the pH levels dropped by 0.10 ( p < 0.05). In pork liver pâtés, the pH values were unaffected by the addition of Spirulina at a dosage of 2.5% [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When Laminaria japonica (Sea tangle) powder was added to patties [ 22 ] and breakfast sausages [ 23 ] in a concentration of 5% and 4%, respectively, the pH levels dropped by 0.10 ( p < 0.05). In pork liver pâtés, the pH values were unaffected by the addition of Spirulina at a dosage of 2.5% [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The type and quantity of the polysaccharides in algae’s dietary fiber fractions will determine their gelation ability [ 27 ]. Therefore, the incorporation of 2% of Spirulina significantly increased (54%) the water-holding capacity (WHC) of pâté samples [ 24 ]. Also, Widati et al [ 19 ] reported that the addition of Eucheuma cottonii flour (5%) significantly increased the WHC in Indonesian-style beef meatballs and reduced the cooking loss (CL) compared to control batches without algae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations